UPAYA PREVENTIF YANG HARUS DILAKUKAN PERBANKAN SYARIAH DALAM MENJAGA KREDIBILITAS DAN KEPERCAYAAN PUBLIK TERKAIT PRODUK PEMBIAYAAN MURABAHAH, MUSYARAKAH, DAN MUDHARABAH - CITRA SARI, WINDA Citra (Jurnal Akuntansi AKUNESA, 2013)
This study aims to determine the preventive measures that Islamic banking can be done inmaintaining the credibility and public confidence through product murabahah financing,musyarakah, and mudharabah. Research methods used in this study is a qualitative researchmethod with the descriptive analysis techniques. Efforts to do is abide by the Islamic bankingfatwa issued by the Dewan Syariah Nasional as well as avoiding the conventional conceptthat has long been known to the public.KEYWORDS:Syariah Banking, Murabahah, Musyarakah, Mudharabah, Credibility, Public Trust.